MODEL PEMBELAJARAN KONTEKSTUAL DALAM PEMBELAJARAN KETERAMPILAN MEMBACA BAHASA ARAB - Baiq Tuhfatul Unsi; Minnaty Adhimatul Wutsqo (Muróbbî: Jurnal Ilmu Pendidikan, 2023)
Based on the fact, many students feel bored and feel Arabic as a difficult subject. Students will learn well if they can construct their own understanding of what is learned. Because learning is an intellectual activity that can generate ideas through observation and build new knowledge. In order for students' applicable learning experiences to be stronger, learning is needed which gives students the opportunity to do, try, and experience it for themselves. So a teacher must be good at choosing the right learning model. Contextual learning models will be able to assist teachers in providing applicative experiences and abilities in student learning. So as to form students who are more active, creative and productive. CTL learning is a learning concept that assumes that learning will be more meaningful if students learn and experience what they learn for themselves, not just knowing, and aims to equip students with flexible knowledge. This study uses descriptive qualitative research methods, namely research that describes existing phenomena, both natural phenomena and human engineering. The results of this research are that in its application, the teacher prepares material and methods and for the next the teacher carries out the initial learning activities and core activities as well as evaluation as the final activity. The supporting factor of this study is the existence of madrasah at the Darissulaimaniyyah Islamic boarding school. High student motivation, different educational backgrounds of students. Varied learning activities. While the inhibiting factors are differences in the level of intelligence of students, differences in educational backgrounds of students, limited time availability